2020
DOI: 10.1101/2020.06.08.138602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Modeling of CDK9 Inhibitors to Explore Selectivity and Structure-Activity Relationships

Abstract: Cyclin-dependent kinase 9 (CDK9) plays a key role in transcription elongation, and more recently it was also identified as the molecular target of a series of diaminothiazole compounds that reverse epigenetic silencing in a phenotypic assay. To better understand the structural basis underlying these compounds' activity and selectivity, we developed a comparative modeling approach that we describe herein. Briefly, this approach draws upon the strong structural conservation across the active conformation of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 90 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…al. have identified the catalytically primed structures (BLAminus) from the PDB to create a comparative modeling pipeline for the ligand bound structures of CDK kinases [28]. Paul and Srinivasan have done structural analyses of pseudokinases in Arabidopsis thaliana and compared with typical protein kinases by applying our conformational labels [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. have identified the catalytically primed structures (BLAminus) from the PDB to create a comparative modeling pipeline for the ligand bound structures of CDK kinases [28]. Paul and Srinivasan have done structural analyses of pseudokinases in Arabidopsis thaliana and compared with typical protein kinases by applying our conformational labels [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental and computational studies have reported applying the nomenclature from our previous work in structural analyses of kinases [11]. Lange and colleagues have solved the crystal structure of the pseudokinase IRAK3 (PDBID 6RUU) and identified its conformation as BLAminus, similar to the active state of a typical protein kinase [12] [28]. Paul and Srinivasan have done structural analyses of pseudokinases in Arabidopsis thaliana and compared with typical protein kinases by applying our conformational labels [14].…”
Section: Discussionmentioning
confidence: 99%
“…Because crystal structures were not available for foretinib bound to p38α or p38δ, these were generated via comparative modeling. The complete protocol for building these models is described in the context of a separate study [73].…”
Section: Pdb Structures Used In Calculationsmentioning
confidence: 99%
“…For clarity we will refer to each of these inhibitors by their names in PubChem. The five inhibitors are: 1) MC180295, a selective CDK9 inhibitor built on a diaminothiazole core [38,39] (PDB ID 6W9E)…”
Section: Resultsmentioning
confidence: 99%
“…Simply put, the chemical space available by enumerating these reactions is far larger than can be explored via "wet" medicinal chemistry. [39]. The rank of each analog in our screen is provided relative to the complete enumerated library (Figure 7).…”
Section: Screening Huge Chemical Librariesmentioning
confidence: 99%